(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe the current status of professional attitudes and identify associated factors among undergraduate nursing students at the Hanoi Medical University campus in Thanh Hoa province in 2025. Methods: A cross-sectional descriptive study was conducted on 203 nursing students from the first to final academic years between June 2025 and May 2026, using a self-administered questionnaire. Data were analyzed using SPSS version 26.0 software, applying descriptive statistics and multivariable logistic regression with a significance level of p < 0.05. Results: The proportion of students with positive professional attitudes was 86.2% (3.84 ± 0.35). Factors significantly associated with positive attitudes included good academic performance (OR = 9.517; p = 0.029), prior experience in patient care (OR = 3.094; p = 0.031), choosing the nursing profession based on personal interest (OR = 4.374; p = 0.030), and inspiration from professional role models (OR = 4.054; p = 0.014). In contrast, exposure to non-official information sources was negatively associated with professional attitudes (OR = 0.200; p = 0.003). Conclusions: The majority of nursing students at the Hanoi Medical University campus in Thanh Hoa province exhibited a positive professional attitude. Academic performance, prior caregiving experience, career choice based on personal interest, and inspiration from successful role models were identified as significant determinants of students’ professional attitudes.